2016
DOI: 10.11114/jets.v4i11.1912
|View full text |Cite
|
Sign up to set email alerts
|

Food Ration and Mental Training for the Improvement of the Free Throw Performance in Congolese Beginners Basketball Players

Abstract: Pôle d'excellence de l'AUF; Formation Doctorale transformation alimentaire des agro ressources T2A, Faculté des sciences et techniques de l'université Marien NGOUABI, Congo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, in Congo Brazzaville, few studies have been conducted on the diet of elite footballers [11], long-distance and middledistance runners [12,13]. These studies have shown the importance of combining diet with sports practice in order to achieve good performance.…”
Section: Problemmentioning
confidence: 99%
“…However, in Congo Brazzaville, few studies have been conducted on the diet of elite footballers [11], long-distance and middledistance runners [12,13]. These studies have shown the importance of combining diet with sports practice in order to achieve good performance.…”
Section: Problemmentioning
confidence: 99%